Effect of surface modified liposomes on the aggregation of platelets and tumor cells - Keil, Claudia; Zeisig, Reiner; Fichtner, Iduna (Thrombosis and Haemostasis, 2005)
Metastasis is still the most serious reason for the high mortality of cancer patients. It is a complex process in which platelets play a crucial role. Several attempts have been performed to inhibit the metastatic process, some of these using modified liposomes. The aggregation behaviour of human platelets and HT29 colon carcinoma cells in the presence of liposomes with a modified surface has been investigated in the present study. Liposomes (PC/CH/DMPE) were unmodified, sterically stabilized by polyethylene glycol (PEG-DSPE), or equipped with the carbohydrate ligand sialyl LewisX (conjugated to PEG-DMPE or DMPE as anchor) intended to specifically compete with ligands expressed by HT29 cells. We found in vitro that an addition of surface modified liposomes to human platelets in plasma caused an up to 2.9-fold increase in platelet aggregation. In addition, when HT29 tumor cells were mixed with platelets and surface modified lipo somes, the number of tumor cells found in aggregates increased significantly from 8.3 % (only tumor cells) to 30.2 %. This result was supported by fluorescence micrographs demonstrating a strong association of platelets and liposomes around the tumor cells. In addition, a clear decrease in number and a change in the distribution of metastases after intravenous injection of HT29 cells in combination with liposomes was observed in vivo. While in control mice metastases in lung, liver and in intestine were prevailing, liposomal treatment resulted in a new localization of metastases in muscles. Taking together, the ability of surface modified liposomes to enhance aggregate formation of platelets and tumor cells has been demonstrated for the first time. The capability of these vesicles to interfere with the metastatic process might have implications for the use of such liposomes for therapeutic applications.
Keywords: Liposomes; sialyl Lewis X; platelets; metastasis